MANAJEMEN SUPERVISI PENDIDIKAN DI MTS ANWARUL HASANIYYAH - Aisya Nur Faradila; Dona Sholehah; Halimah Halimah; Syahrani Syahrani (CV. ADIBA AISHA AMIRA, 2023)
Efforts to improve the quality of education will greatly depend on the management used in the educational institution concerned. This management will be effective and efficient if supported by professional human resources to operate the educational institution, the ability of the school principal to lead, the ability and commitment of reliable educational staff, adequate facilities and infrastructure to support teaching and learning activities, as well as achievements student. If one of the things above is not as expected and/or does not function as it should, then the effectiveness and efficiency of the management of the educational institution/school is less than optimal. This research aims to determine the management of educational supervision at MTs Anwarul Hasaniyyah (ANWAHA) in Haruai sub-district, Tabalong district.